Fast-synthesis and catalytic property of heterogeneous Co-MOF catalysts for the epoxidation of α-pinene with air. (7th October 2020) - Zhang, Haifu; He, Jie; Lu, Xinhuan; Yang, Lu; Wang, Chenlong; Yue, Fanfan; Zhou, Dan; Xia, Qinghua
Abstract : A method for synthesizing Co-MOF by rapidly rotating hydrothermal crystallization is proposed. When the rotation speed was 150 rpm, only 2 h was needed to synthesize Co-MOF-150-2 with high catalytic activity and stability. Abstract : In the past decades, many methods have been developed for synthesizing MOFs, including solvothermal synthesis, mechanical synthesis, electrochemical synthesis, and microwave synthesis. Based on the existing research, a method is proposed for synthesizing Co-MOF by rapidly rotating hydrothermal crystallization, which largely shortens the crystallization time of Co-MOF. When the rotation speed was 150 rpm, only 2 h of crystallization time was needed to synthesize Co-MOF-150-2 with high crystallinity and stability. The optimal Co-MOF-150-2 manifested remarkable activity and selectivity for the epoxidation of α-pinene under mild conditions. The catalytic conversion of α-pinene reached the highest over the Co-MOF-150-2 catalyst, in which the conversion of α-pinene was 99.5% and the yield of 2, 3-epoxypinane was 95.7%. The Co-MOF materials synthesized by the rotary method also had excellent stability and highly catalytic activity in recycling experiments.